1996
DOI: 10.1177/000331979604700505
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Evaluation Of Right Ventricle Systolic Pressure During Dynamic Exercise by Saline-Enhanced Doppler Echocardiography in Progressive Systemic Sclerosis

Abstract: Progressive systemic sclerosis (PSS) is characterized in its first phases by vascular damage. Lungs are involved in two thirds of patients with initial progressive destruction of the capillary bed and consequent reduction of the functional reserve, which may lead to hypertension of the pulmonary circulation. For these reasons it is of great interest to have early information about the pressure of the pulmonary circulation, both at rest and during exercise, to follow the progression and the evolution of the ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…As LV function was not affected, it was difficult for the authors to attribute the abnormalities of RV diastolic function to myocardial fibrosis and ischemia due to intermittent coronary vasospasm alone. They assumed that the most probable cause is mild or early intermittent pulmonary arterial hypertension since Doppler echocardiography may underestimate RV pulmonary pressure calculated from transtricuspid pressure gradient [40-42]. In agreement with Lindqvist et al, we obtained pulmonary arterial pressure from a single measurement at rest.…”
Section: Discussionsupporting
confidence: 82%
“…As LV function was not affected, it was difficult for the authors to attribute the abnormalities of RV diastolic function to myocardial fibrosis and ischemia due to intermittent coronary vasospasm alone. They assumed that the most probable cause is mild or early intermittent pulmonary arterial hypertension since Doppler echocardiography may underestimate RV pulmonary pressure calculated from transtricuspid pressure gradient [40-42]. In agreement with Lindqvist et al, we obtained pulmonary arterial pressure from a single measurement at rest.…”
Section: Discussionsupporting
confidence: 82%
“…56 In SSc, studies have suggested a high prevalence of exercise-induced PAH (EIPAH). 57,58 Steen et al 59 evaluated 54 patients with SSc at high risk for PAH and identifi ed EIPAH by TTE in 24. Of these, 19% had resting PAH, and 62% had EIPAH on RHC.…”
Section: Vasodilator Testingmentioning
confidence: 99%
“…Thus, during mild exercise, pulmonary-artery pressure was much higher in patients with CMS than in controls (Fig. 6.1b ) and the pressure gradient difference between the 2 groups was more than three times greater than at rest [ 47 ]. During exercise, the arterial oxygen saturation decreased signifi cantly in both groups, but the exercise-induced decrease tended to be greater in patients than in controls.…”
Section: Exaggerated Exercise-induced Pulmonary Hypertension In Cmsmentioning
confidence: 86%
“…To test this hypothesis, we measured pulmonary-artery pressure at rest and during mild semi-supine bicycle exercise in patients suffering from CMS and normal control subjects who were all born and permanently living at 3600-4000 m [ 47 ]. To discriminate between anatomical and functional defects, we measured the carbon monoxide diffusion capacity (a proxy of the extent of the pulmonary microcirculation) and we tested the effects of nitric oxide inhalation on pulmonary-artery pressure in the two groups.…”
Section: Exaggerated Exercise-induced Pulmonary Hypertension In Cmsmentioning
confidence: 99%